Níveis cardíacos de troponina I em pacientes com epilepsia do lobo temporal refratária após cortico-amígdalo-hipocampectomia - Colugnati, Diego Basile [UNIFESP] (2007)
PURPOSE: Sudden unexpected death in epilepsy (SUDEP) is the main cause of death in patients with epilepsy. Morphologic and functional changes in the heart are related to SUDEP. The aim of our study was to verify the concentration of troponin I, an important marker of myocardium damage, in patients with temporal lobe epilepsy who were submitted to surgical resection and were not seizure-free after the procedure. METHODS: Eleven non-consecutive patients participated in the study and all of them presented poor seizure control after surgical procedure. Troponin I levels higher then 1 ng/ml indicate myocardium damage. The detection level of the kit used in our study was 0,15 ng/ml. RESULTS: Only three patients showed detectable troponin I levels. The troponin I levels found in our study is not related with sex, age or side of the lesion. CONCLUSIONS: In spite of we did not find positive results in our study, an active role of the heart in SUDEP cannot be discarded, since some injuries, even so not being capable to modify troponin I levels, can be enough to generate arrhythmogenic foci.